Conservation Biology Courses With A Local Wisdom Approach In Forming Environmental Care Attitudes And Environmental Problem Solving Ability - Armanda, Fahmy; Dekar, Muhammad; Saputri, Wulandari (Sean Institute, 2024)
Conservation Biology lectures are a subject in education that provides students with the experience to understand the concepts of biodiversity, issues and efforts in biological heritage conservation, mitigation, solutions, and promotion of conservation efforts, as well as collaboration with stakeholder involvement in conservation efforts. This course requires students to develop an environmental and conservation awareness attitude as well as problem-solving skills related to environmental damage and biodiversity loss. This study aims to analyze environmental awareness and problem-solving skills arising from environmental damage and biodiversity loss. The research method used is descriptive qualitative, and data is collected through observation, questionnaires, interviews, and essay questions. The results of this study show that environmental awareness and problem-solving skills related to environmental issues are at a high level. It is hoped that the results of this study can serve as a foundation for the development of conservation biology lectures to foster environmental awareness and problem-solving skills related to environmental damage and biodiversity loss issues, thereby supporting the benefits of conservation biology education.